Humidity Sensing Properties of Surface Modified Polyaniline Metal Oxide Composites - S. C. Nagaraju; Aashis S. Roy; J. B. Prasanna Kumar; Koppalkar R. Anilkumar; G. Ramagopal (Journal of Engineering)
Polyaniline- (PANI) praseodymium Oxide (Pr2O3) composites have been synthesized by in situ polymerization method with different weight percentages. The synthesized composites have been characterized by Fourier transform infrared spectroscopy, X-ray diffraction and scanning electron microscopy. The temperature dependent conductivity shows that the conductivity is due to the hopping of polarons and bipolarons. These composites show negative thermal coefficient (α) behavior as a function of temperature, which is characteristic behavior of semiconducting materials. Sensor studies have been carried out by two-probe method and found that the sensitivity increases with increase in % RH. It is noticed that stability increase is due to the presence of Pr2O3 in polyaniline up to 30 wt%. A fast recovery and response time along with high sensitivity make these composites suitable for humidity sensors.